Warisan Budaya, Pariwisata dan Pembangunan di Muarajambi, Sumatra - Devi Roza K. Kausar (Fakultas Pariwisata Universitas Pancasila, 2013)
This paperis part ofapreliminary studyon the potentialsand problemsin the development ofheritage tourismasa rural and regional development strategyinMuarajambi. Itaimsto presentthe variousdynamicsin the relationshipbetweentourism, culturalheritage, anddevelopment through Muarajambi’s case. This studyusesqualitative dataobtainedthroughfield observations,interviews, secondarydata collectionandliterature studies. It concludes that the development of certain economic sectorswithin the heritage area causes disruption toheritage conservation and limits heritage tourism development. The study suggests that the area must be declared as heritage conservation area through appropriate legalframework and that clear coordination mechanism between central and local governments that aim toward conserving heritage for communities’ welfare should be realized. Keywords: cultural heritage, tourism, development